A phytosociological analysis of abandoned olive-rove grasslands of Ausoni mountains (Tyrrhenian district of Central Italy) - di Pietro, Romeo; Blasi, Carlo (Lazaroa, 2002)
Over the last fifty years, about 80% of Olea europea L. cultivations in the submediterranean belt of Central Italy have been abandoned and they are now subjected to new colonizations from surrounding wild vegetation. A phytosociological study of the main types of grassland communities occurring in this «vanishing» typically mediterranean landscape is presented here. The Ausoni Mountains, a Tyrrhenian coastal chain of central Italy were selected as a study area. Distribution of secondary grassland communities is influenced by the combined action of many factors, such as bioclimatic parameters, soil characteristics, time since abandonment, land use pattern. In the warmest sites, the early successional stages are characterized by Hyparrhenia hirta open dry grasslands. This community is gradually replaced by dense steppe-like grasslands very poor in species, dominated by Ampelodesmos mauritanicus (Psoraleo-Ampelodesmetum) or less frequently by Hyparrhenia hirta again. Both the inland areas and the north facing slopes are characterized by Festuco-Brometea communities. Perennial grasses, in particular Brachypodium rupestre (Galio-Brachypodietum) dominate these environments, and annual species are confined to restricted areas, such as trampled sites or terrace boundaries (Crucianello-Hypochoeridetum). Two new associations (Galio lucidi-Brachypodietum rupestris and Thymo vulgaris-Hyparrhenietum hirtae) are presented in this paper.